Vitamin D deficiency in long‐term hospitalization psychiatric wards in an equatorial nation. (25th April 2020) - Suri, Tarun; Suri, Sandeep; Poremski, Daniel; Fang, Tina; Su, Alex
Abstract: Introduction: Vitamin D deficiency and insufficiency have been shown to be prevalent in several populations, including in people who have a mental illness. Deficiency has been linked to specific mental health sequelae. Furthermore, deficiency may be perpetuated by medications routinely prescribed to people with severe mental illness. Therefore, symptoms of mental illness may be exacerbated by deficient levels of vitamin D, and treatments for mental illness may exacerbate deficiency. This study sought to determine the vitamin D levels of people hospitalized for a period longer than a year in an equatorial nation, Singapore. The inpatient population was then categorized according to levels to determine the need for supplementation. Methods: Total 25‐hydroxy vitamin D in serum and plasma levels were tested in 403 individuals in long‐term psychiatric wards. Blood serum and plasma levels were classified into three groups. Regression models were constructed to test the associations between levels and clinical covariates. Results: Forty (9.9%) people had vitamin D levels that were sufficient. A link was found between vitamin D levels and medications given for gastrointestinal illnesses (β −2.48, p = .014, 95%CI ‐4.46 to‐0.51) and between vitamin D levels and length of stay (β −0.13, p = .027, 95%CI ‐0.24 to‐0.01). No other relationships were statistically significant. Discussion: Despite its geographic location and opportunities for regular outdoor activity, vitamin D deficiency, and insufficiency are prevalent among people hospitalized for long periods of time in an equatorial nation. The level of deficiency is comparable to those observed in other settings.